Relationships of the Dzungar Khanate with the Neighboring Peoples of Central Asia in the XV-First Half of the XVIII Century - A. Sh. Kadyrbaev (Nomadic Civilization: Historical Research, 2023)
The article is devoted to an actual problem — the analysis of the history of the formation of relations between the states of Central Asia and East Turkestan (the Uzbek khanates and Mogolistan), as well as the Kyrgyz tribes of the Tien Shan, Fergana and Pamir, with the Dzungar Khanate (the nomadic state of the Oirats) in the XV-first half of the 18th century on the basis of the introduction of archival materials and multilingual sources into scientific circulation. The relevance of this issue is explained by its limited historiographic tradition, since there are no special studies on this issue in the modern period. In addition, the relevance of studying this problem urgently requires an interdisciplinary and civilizational-cultural approach. The purpose of the work is a comprehensive description of the development of relations between the Oirats of the Dzungar Khanate, on the one hand, and the settled agricultural states of the Muslim peoples of Maverannahr, Khorezm, Fergana, East Turkestan, and the Kirghiz, on the other, which will shed light on the dramatic events that had such an important impact on the historical fate of these peoples. To achieve this goal, the author presented information on this issue, gleaned from various sources and subjected to scientific analysis in domestic and foreign historiography. The chronological framework of the study chosen by the author is quite consistent with the task, since it allows us to analyze the relationship with the indicated neighboring peoples and their role in the history of the Kalmyks and Oirats.